Gender & Sexuality Among Anabaptists - Brown, Joshua; Herlitzke, Hunter (My University, 2018)
In June 2014, a group of Lesbian, Gay, Bisexual, Transgender, Queer-identifying ex-Amish individuals rode on a float with Miss Kalamazoo Pride LaDonna Divine in Michigan’s Pride Parade. This event was the first and only public gathering of LGBTQ Amish in the history of the nearly 500-year-old religion. The life stories of these individuals have been largely ignored and under-researched. Amish settlements range from more liberal communities to more conservative. In liberal communities the Amish may have running water in their houses, use cellphones, or even use solar power. In conservative communities they may not even have running water or anything. But one thing they both have in common is that they do not sanction homosexuality. They barely even talk about sexual intercourse between a man and a woman.
Color poster with text, images, and photographs
Keywords: Amish; Sex role; Gender identity; Posters